Bactericidal antibody response to Pseudomonas aeruginosa by adults with urinary tract infections. - Smalley, D L (1979)
In this investigation we found that adults with upper urinary tract infections caused by Pseudomonas aeruginosa produced serum antibodies with bactericidal activity against the bacterium. Seventeen of 20 infected adults showed bactericidal activity with a titer range of 1:10 to 1:10,000.